2005
DOI: 10.1002/pssa.200460184
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and atomic relaxation processes in irradiated cryocrystals

Abstract: Relaxation processes and stability of charge centers in preirradiated cryocrystals doped with atomic and molecular species are discussed. The study was performed combining techniques of spectrally resolved thermally stimulated luminescence (TSL), thermally stimulated exoelectron emission (TSEE) and photonstimulated exoelectron emission (PSEE). Comparison of the yields of electrons and photons in VUV and visible ranges made it possible to discriminate between reactions of charge carriers and neutral reactive sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The first results demonstrating reliability of this mechanism are presented in [14]. The experiments on stimulation of relaxation processes by laser light [2,15] provide an additional proof of the mechanisms discussed.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The first results demonstrating reliability of this mechanism are presented in [14]. The experiments on stimulation of relaxation processes by laser light [2,15] provide an additional proof of the mechanisms discussed.…”
Section: Methodsmentioning
confidence: 86%
“…Very often electronic and atomic relaxation processes occurring in pre-irradiated solids are considered separately ignoring the interconnection between these channels of relaxation. Our recent studies demonstrated the fundamental importance of the interconnection between atomic and electronic processes in the formation and branching of relaxation paths [2].…”
Section: Introductionmentioning
confidence: 92%
“…This reaction is followed by the emission of visible light called by chemiluminescence. This process was considered to be a source of the energy needed for electron detrapping (Savchenko and Bondybey, 2005). So one can expect the sputtering from pre-irradiated RGS induced by photons.…”
Section: Resultsmentioning
confidence: 99%
“…Electrons can be releazed from the traps by photons of appropriate energy and promoted into the conduction band [51]. Such photomobilized electrons participate in exoelectron emission [51][52][53], react with holes producing luminescence [42,54,55] and anomalous low-temperature post-desorption from the cryocrystal surfaces [45,56].…”
Section: "Cold" and "Hot" Thermoluminescence Spectra From Ihcsmentioning
confidence: 99%